Advertising, investor attention, and stock prices: Evidence from a natural experiment. Issue 1 (2nd September 2020) - Mayer, Erik J.
Abstract: I test whether advertising affects stock prices through an investor attention channel. I use corporate sponsorships of college football bowl games as a natural experiment that provides variation in advertising exposure that is unrelated to firm fundamentals. Sponsoring firms' stocks experience large increases in investor attention, abnormally high turnover, and temporary price pressure that is related to bowl games' TV‐ratings and score differentials. Retail investors are net buyers of sponsors' stocks, whereas institutional investors initially remain neutral and then start selling, ultimately driving a reversal toward fundamental values. These findings shed light on who wins/loses when advertising attracts investor attention.